2008
DOI: 10.3171/jns/2008/109/9/0439
|View full text |Cite
|
Sign up to set email alerts
|

Terson hemorrhage in patients suffering aneurysmal subarachnoid hemorrhage: predisposing factors and prognostic significance

Abstract: Terson hemorrhage constitutes a common SAH-associated complication. Its incidence is increased in patients with low GCS and high WFNS scores, and high Hunt and Hess and Fisher grades. Its presence is associated with increased mortality and morbidity rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
79
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(84 citation statements)
references
References 21 publications
1
79
0
1
Order By: Relevance
“…Terson syndrome now encompasses any intraocular hemorrhage associated with intracranial hemorrhage and elevated intracranial pressures (2)(3)(4), which often results in significant morbidity and subsequent decreased quality of life. Vitrectomy has been proposed to have a role in treating Terson syndrome, and numerous studies have reported good visual recovery following surgery (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Terson syndrome now encompasses any intraocular hemorrhage associated with intracranial hemorrhage and elevated intracranial pressures (2)(3)(4), which often results in significant morbidity and subsequent decreased quality of life. Vitrectomy has been proposed to have a role in treating Terson syndrome, and numerous studies have reported good visual recovery following surgery (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Terson's syndrome is reported to occur in 2.6 to 27% of patients following SAH, depending on how carefully the diagnosis is sought 8 . Patients with subhyaloid hemorrhage generally complain of scotoma as compared to those with vitreous hemorrhage, who report blurred vision and floaters.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with subhyaloid hemorrhage generally complain of scotoma as compared to those with vitreous hemorrhage, who report blurred vision and floaters. Typically, patients with TS have a worse clinical SAH grade on admission 6,8 , likely in part due to the sudden increase in ICP required to cause intraocular hemorrhage. The acute increase in ICP immediately following SAH may last only a few minutes 9 , and the anterior communicating artery location adjacent to the optic nerve sheath may allow for a more focal increase in ICP without generalized cerebral injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations